Study of the Implementation Restoration Concept in the Criminal Justice System in Indonesia - Mashendra, Mashendra; Ibrahim, Kayode Muhammed; Salam, Safrin; Nurcahyo, Edy; Chatimah, Nurul Ambiyaa (Faculty of Law, Universitas Pattimura, 2024)
Introduction: The Indonesian Criminal Justice System does not recognize concepts related to restoration, such as restorative justice, alternative conflict resolution, circular punishment, or ishlah. The idea of restoration is generally not recognized by the Criminal Procedure Code (KUHAP), which is based on the concept of legality.Purposes of the Research: To study and discuss the actual existence of the function and impact of the concept of restoration (restorative justice, alternative dispute resolution, circular punishment, and circular punishment or Ishlah) in the development of the Indonesian Criminal Justice System.Methods of the Research: This research uses a normative research methodology with a qualitative approach to investigate the concept of restoration and its consequences for various applicable laws and principles.Results of the Research: The findings of this research show that the concepts of recovery and restoration, such as alternative dispute resolution and punishment, are concepts that prioritize the interests of the parties involved, especially the principles of win-win solutions and recovery. This has been used to resolve criminal cases that meet standards at both the investigation and prosecution levels as one way to resolve criminal cases. The application of these ideas in the Indonesian Criminal Justice System is a deviation from the basic principles of the Criminal Procedure Code, namely the principle of legality which must be observed at all times. It is recommended that methods for implementing restorative ideas be included in the Draft Criminal Procedure Code (RKUHAP). Some examples of this mechanism are alternative dispute resolution, circular punishment, and ishlah. Thus, the concept of restoration can be legally and formally recognized as a principle in the Indonesian Criminal Justice System when put into practice.